Strut-and-tie modeling of two-dimensional reinforced concrete structural elements - Zhao, Yiwen (2008)
This thesis focused on the applicability of truss models and the strut-and-tie method to the analysis and design of reinforced concrete beams and structural walls with opening that had complicated internal stress flow and to develop a design procedure for these beams and walls based on such models.